Radical innovation in medium-sized enterprises: an exploratory study of strategic intent and innovation process. (1st January 2012) - DeMartino, Richard; Neck, Heidi M.; Dwyer, Patricia A.; Treese, Connie
There is a significant and growing body of research on radical innovation as a path to corporate renewal and growth. Despite this existing literature, very little is known regarding the role of radical innovation in medium-sized enterprises (MSEs). The vast majority of radical innovation knowledge emerges from research on large established companies. Employing a qualitative and exploratory methodology to examine the radical innovation efforts in nine MSEs, we found that radical innovation tends to be narrowly defined, closely aligned with current businesses, and market-driven. Processes are both formal and ad-hoc but in general lack separation from incremental innovation processes.